A systematic review of vitamin D status in populations worldwide - Hilger, Jennifer; Friedel, Angelika; Herr, Raphael M.; Rausch, Tamara; Roos, Franz; Wahl, Denys A.; Pierroz, Dominique D.; Weber, Peter; Hoffmann, Kristina (British Journal of Nutrition, 2014)
Vitamin D deficiency is associated with osteoporosis and is thought to increase the risk of cancer and CVD. Despite these numerous potential health effects, data on vitamin D status at the population level and within key subgroups are limited. The aims of the present study were to examine patterns of 25-hydroxyvitamin D (25(OH)D) levels worldwide and to assess differences by age, sex and region. In a systematic literature review using the Medline and EMBASE databases, we identified 195 studies conducted in forty-four countries involving more than 168000 participants. Mean population-level 25(OH)D values varied considerably across the studies (range 4·9-136·2nmol/l), with 37·3% of the studies reporting mean values below 50nmol/l. The highest 25(OH)D values were observed in North America. Although age-related differences were observed in the Asia/Pacific and Middle East/Africa regions, they were not observed elsewhere and sex-related differences were not observed in any region. Substantial heterogeneity between the studies precluded drawing conclusions on overall vitamin D status at the population level. Exploratory analyses, however, suggested that newborns and institutionalised elderly from several regions worldwide appeared to be at a generally higher risk of exhibiting lower 25(OH)D values. Substantial details on worldwide patterns of vitamin D status at the population level and within key subgroups are needed to inform public health policy development to reduce risk for potential health consequences of an inadequate vitamin D status. © 2013 The Authors.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Populations; Public health; Vitamin D